2022
DOI: 10.1177/1071181322661345
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Crash Risks and Driving Performance Among the Oil and Gas Industry Workers

Abstract: Motor vehicle crashes are the major cause of worker injuries and fatalities in the oil and gas industry. The current study uses an online survey to investigate driving safety and crash risk among the oil and gas industry workers. We examine driver characteristics and attentional and cognitive abilities associated with increased crash risks and evaluate the frequency of traffic warnings, tickets, crashes, and near-crashes among this driver population. The preliminary results from this ongoing study suggest a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…However, tailgating as a cause of collisions and running signs and signals both increased injury rates. Previous studies have identified the violation of traffic signals and signs as significant contributors to accidents [48,51,52]. Moreover, closely following another vehicle with a short braking distance was found to be a critical factor impacting injuries [53].…”
Section: Cause Of Assumption Factormentioning
confidence: 95%
“…However, tailgating as a cause of collisions and running signs and signals both increased injury rates. Previous studies have identified the violation of traffic signals and signs as significant contributors to accidents [48,51,52]. Moreover, closely following another vehicle with a short braking distance was found to be a critical factor impacting injuries [53].…”
Section: Cause Of Assumption Factormentioning
confidence: 95%